The association between serum phosphorus and common carotid artery intima–media thickness in ischemic stroke patients - Du, Huaping; Guo, Tingting; Ye, Huan; Bao, Yingshi; Qiu, Zhuoyin; Sun, Yaming; You, Shoujiang; Liu, Yuan; Xu, Yuan; Zhang, Chunqing; Qiu, Chunfang (Frontiers in Neurology, 2023)
Purpose: Elevated phosphorus concentrations are associated with an increased risk of atherosclerosis and cardiovascular diseases. Common carotid artery intima-media thickness (cIMT) is an imaging marker of atherosclerosis. However, data on the relationship between phosphorus and cIMT is rare in ischemic stroke. We aimed to evaluate the association between serum phosphorus levels and cIMT in patients with ischemic stroke. Patients and methods: A total of 1,450 ischemic stroke patients were enrolled. Participants were divided into four groups according to baseline serum phosphorus quartiles. Carotid atherosclerosis was identified by measurement of cIMT, and abnormal cIMT was defined as having a maximum cIMT and mean cIMT value ≥1 mm. Multivariable logistic regression models were used to assess the association between serum phosphorus levels and the presence of abnormal cIMT. Results: In the multivariable-adjusted analysis, the highest serum phosphorus quartile (Q4) was associated with a 2.00-fold (adjusted odds ratio [OR] 2.00; 95% confidence interval [CI] 1.44-2.79) increased risk of having abnormal maximum cIMT and 1.76-fold (adjusted OR 1.76; 95% CI 1.22-2.53) increased risk of having abnormal mean cIMT in comparison to Q1, respectively. Furthermore, the association between serum phosphorus and abnormal cIMT was confirmed with serum phosphorus as a continuous variable and in subgroup analyses. Conclusion: In patients with acute ischemic stroke, baseline elevated serum phosphorus levels were independently associated with carotid atherosclerosis measured by cIMT.